Association between body image perception with demographic characteristics of physically active individuals during COVID-19 lockdown in Saudi Arabia - AlMarzooqi, Mezna A. (Frontiers in Sports and Active Living, 2022)
Abstract: Objective: The study aims to determine the relationship between body image perception and demographic factors among physically active (men and women) during the COVID-19 lockdown in Saudi Arabia. Methods: A descriptive cross-sectional survey was employed among physically active individuals in Saudi Arabia between June to July 2020. Eligible participants completed a 19- item self-administered questionnaire that covered three areas: demographic questions, reasons for physical activity, and role or perceptions of body image during the COVID-19 pandemic quarantine. Results: A total of 323 physically active individuals participated in this study. The majority of the participants were female (N=217, 72.7%), were married (66.6%), and living in the Middle region of Saudi Arabia (N= 268, 83%). The analysis shows that majority of the participants were dissatisfied with their current body shape. The analysis also showed a significant association between participants' educational attainment and BMI and body dissatisfaction (p= 0.001). The strongest predictor was BMI level, recording an odds ratio of 5.99 (CI: 2.15 – 10.54, p=0.001) in obese and overweight with an odds ratio of 4.55 (CI: 1.31 – 9.35, p=0.001), indicating that compared with normal weight, obese and overweight participants were more likely to be dissatisfied by five and four times respectively. Conclusion: The present study indicates that physically active individuals are greatly influenced by the confinement period. Programs that promote physical activity in their house or during lockdown may help to encourage, lessen their anxiety and maintain their health. This may also decrease the anxiety of individuals, particularly those active ones.